An analysis of The Star and The New Straits Times global Islamic news / Siti Hajar Abd Aziz, Noor Mayudia Mohd Mothar and Shahril Anuar Abdul Ghalim - Abd Aziz, Siti Hajar; Mohd Mothar, Noor Mayudia; Abdul Ghalim, Shahril Anuar (Research Management Institute (RMI), 2010)
Malaysian media received their world news from the international news agencies; therefore readers are flooded with news reports structured by the Westerns point ofvielv. This paper wishes to investigate the portrayal of Islam in news selected and republished in the World section of The Star and the New Straits Times. A content analysis revealed that most ofthe stories on Islam are revolved around war, crime and politics. News on Islam has reported that this religion been relatively associated with violence; suggesting that the news agencies are bias as reporting on Islam, especially in the news republished by The Star. The main frames projected in The Star are "Islam is inherently violent" and "Islam does not go well with the concept of peace ". Although news reports in NST suggested that terrorism and wars are common in the Islamic countries, yet the tones suggested that Islam is not the source of the act of extremism. The mainframes in NST are "terrorism and warsare common in the Islamic countries, yet Islam is not to be blamed" and "the Muslim countries are slowly moving from extremism to peace and moderation. The finding indicates that there English newspapers are forced to republished negative news on Islam which will resulted in a misconception of Islam among the readers.